2015
DOI: 10.1590/1414-431x20154506
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 99mTc-HYNIC-βAla-Bombesin(7-14) as an agent for pancreas tumor detection in mice

Abstract: Pancreatic adenocarcinoma is important in oncology because of its high mortality rate. Deaths may be avoided if an early diagnosis could be achieved. Several types of tumors overexpress gastrin-releasing peptide receptors (GRPr), including pancreatic cancer cells. Thus, a radiolabeled peptide derivative of gastrin-releasing peptide (GRP) may be useful as a specific imaging probe. The purpose of the present study was to evaluate the feasibility of using99mTc-HYNIC-βAla-Bombesin(7-14)as an imaging probe for Capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A 99M Tc-labeled-BnR-pan-agonist imaged pancreatic-cancer-cells in xenografts with a 4-fold higher uptake in the tumor-cells than normal cells[201]; a 68 Ga-labeled-BnR-agonist showed enhanced uptake into the pancreatic-cancer cell-lines-AR42J compared to a 68 Ga-RGD-labeled-ligand for avβ3-integrin binding[202]; a 99m Tc-labeled-Bn-agonist imaged colonic-cancer xenografts[203] and a study[103] in which the tumor uptake/cytotoxicity of a 188 Re-labeled-liposomal-Bn-agonist with or without doxorubicin loading in pancreatic-cancer(AR42J cells) xenografts was compared. Treatment with the probe with the doxorubicin resulted in greater survival times and when compared with a probe without 188 Re but with doxorubicin, provided evidence the co-delivery of the 188 Re and doxorubicin had antitumor effect[103].…”
Section: Bn-peptides-bnr: Other Tumorsmentioning
confidence: 99%
“…A 99M Tc-labeled-BnR-pan-agonist imaged pancreatic-cancer-cells in xenografts with a 4-fold higher uptake in the tumor-cells than normal cells[201]; a 68 Ga-labeled-BnR-agonist showed enhanced uptake into the pancreatic-cancer cell-lines-AR42J compared to a 68 Ga-RGD-labeled-ligand for avβ3-integrin binding[202]; a 99m Tc-labeled-Bn-agonist imaged colonic-cancer xenografts[203] and a study[103] in which the tumor uptake/cytotoxicity of a 188 Re-labeled-liposomal-Bn-agonist with or without doxorubicin loading in pancreatic-cancer(AR42J cells) xenografts was compared. Treatment with the probe with the doxorubicin resulted in greater survival times and when compared with a probe without 188 Re but with doxorubicin, provided evidence the co-delivery of the 188 Re and doxorubicin had antitumor effect[103].…”
Section: Bn-peptides-bnr: Other Tumorsmentioning
confidence: 99%
“…Exploring the fact that Capan-1 tumor cell lines express functional GRPr on its membrane surface, Carlesso et al [40] evaluated the feasibility of 99m TcHYNIC-β-Ala-BBN (7–14) to serve as an imaging agent for human pancreatic adenocarcinoma. Biodistribution studies confirmed the radiopeptide was excretion by the urinary tract and had higher tumor-to-muscle values in later times (4 h after injection) while kidney and bladder have lower radiation signals.…”
Section: Radiolabeled Bbn Derivatives In Preclinical Studiesmentioning
confidence: 99%
“…Biodistribution studies confirmed the radiopeptide was excretion by the urinary tract and had higher tumor-to-muscle values in later times (4 h after injection) while kidney and bladder have lower radiation signals. All target/non-target ratios from scintigraphic images and ex vivo biodistribution assay were higher than 1.5, indicating that the formulated imaging agent is able to identify Capan-1 pancreatic adenocarcinoma [40]. 99m TcHYNIC-β-Ala-BBN (7–14) has also been successfully used in scintigraphic studies of other types of tumor models, such as human breast (MDA-MB-231 cells) [28] and colon (HT-29 cells) [41] cancer, in which tumor-to-muscle ratios were up to 6.00 (at 4 h post injection) and up to 11.17 (at 1 h post injection) respectively.…”
Section: Radiolabeled Bbn Derivatives In Preclinical Studiesmentioning
confidence: 99%
“…However, an extra lysine may be coupled to the C-terminal portion in order to maintain the peptide sequence with a minor change. Lastly, to stabilize 99m Tc binding to HYNIC, tricine and ethylenediamine-N,N’-diacetic acid (EDDA) are used as co-ligands in the radiolabeling procedure [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%